Influence of anisotropy on the durability of Madrid-region Cretaceous dolostone exposed to salt crystallization processes - Fort, R.; Fernández-Revuelta, B.; Varas, M. J.; Alvarez de Buergo, M.; Taborda-Duarte, M. (Materiales de Construcción, 2008)
The resistance of dolomitic limestone to salt crystallization processes was studied on materials from Redueña and Torrelaguna in the province of Madrid, Spain. Much of the region’s architectural and monumental heritage was built with the materials from these two sites. Stone specimens were selected for testing on the basis of ultrasonic wave propagation velocity (Vp) measurements taken in around one hundred cubic samples of each variety. The anisotropy indices were calculated and the samples were clustered on the basis of the results. Two representative samples of each class were taken and characterized for their petrographic and petrophysical properties before and after exposure to salt crystallization cycles. Ageing was evaluated in terms of weight loss and the visual deterioration observed. The degeneration pattern found varied substantially in the two materials: the Requena material exhibited more intense deterioration, with scaling and spalling, while the Torrelaguna dolostone tended to generate fragmentation and rounding at corners and edges. The anisotropy of these stones does not appear to clearly govern salt crystallization-mediated deterioration. Although no clear relationship could be established between the intensity of deterioration and the initial anisotropy indices, total anisotropy was observed to increase as a general rule, and normally more than the relative anisotropy index. No specific anisotropic group was found to undergo greater variation than any other.